Reliability analysis for a cold standby system under stepwise Poisson shocks. Issue 1 (2nd January 2021) - Ge, Xin; Sun, Jiali; Wu, Qingtai
ABSTRACT: In this paper, a two-dissimilar-component cold standby repairable system maintained by a repairman is investigated. The system fails due to either intrinsic factors or external shocks. Assume that shocks arrive according to a stepwise Poisson process, the intensity of which varies with respect to the number of failures of the working component. Repair after failure is imperfect. Using the supplementary variable method and the vector Markov process theory, we obtain some important reliability index for the system. By the renewal reward theorem, an optimal replacement policy N ∗ is derived by minimising the average cost rate of the system. Numerical examples are presented to validate the theoretical results.